Exploring The Causes of Stress and Associated Coping Strategies Among Early Childhood Educators in Nigeria: A Structural Equation Model - Ogbeche, Akobi Thomas; Okeke, Chinedu Ifedi (International Journal of Research in Counseling and Education, 2023)
Early childhood educators are particularly confronted with a high level of stress due to the diverse learning needs and peculiarities of children from birth to five years of age. The aim of this study, therefore, was to explore the causes of stress and associated coping strategies among early childhood educators in Nigeria using structural equation modelling. The authors adopted an ex-post-facto research design involving 400 Early Childhood Educators who participated in the study. Two instruments, titled Early Childhood Educators’ Work-Related Stress Questionnaire (ECEWRSQ), and Questionnaire on Cause of Stress and Coping Strategies Among Early Childhood Educators  (QCSCSAECE), were used for data collection. Data were analyzed using SPSS and SmartPLS computer-based statistical software. Results showed that the hypothesized causal model that describes early childhood educators’ stress, causes, and associated coping strategies was significantly supported by the empirical data. It was also revealed that direct action technique, problem-focused and emotion-focused coping strategies have significant (p < 0.05) direct effects on the causes of stress among early childhood educators. The implication of this finding is that early childhood educators need to adopt such strategies in order to deal with some of the causes of stress among them. Hence, it was recommended that early childhood educators should employ direct action techniques, and problem-focused as well as emotion-focused coping strategies in order to overcome their work-related stress.